Answer:
6
Step-by-step explanation:
find a common factor
6*8=48
8*6=48
Answer:
48.7%
Step-by-step explanation:
Answer:
![4(x + 3) + 2x = 6(x + 2)](https://tex.z-dn.net/?f=4%28x%20%2B%203%29%20%2B%202x%20%3D%206%28x%20%2B%202%29)
![5 + 2(3 + 2x) = x + 3(x + 1)](https://tex.z-dn.net/?f=5%20%2B%202%283%20%2B%202x%29%20%3D%20x%20%2B%203%28x%20%2B%201%29)
Step-by-step explanation:
![5(x + 3) + x = 4(x + 3) + 3 \\ 5x + 15 + x = 4x + 12 + 3 \\ 5x + x - 4x = 12 + 3 - 15 \\ 2x = 0](https://tex.z-dn.net/?f=5%28x%20%2B%203%29%20%2B%20x%20%3D%204%28x%20%2B%203%29%20%2B%203%20%5C%5C%205x%20%2B%2015%20%2B%20x%20%3D%204x%20%2B%2012%20%2B%203%20%5C%5C%205x%20%2B%20x%20-%204x%20%3D%2012%20%2B%203%20-%2015%20%5C%5C%202x%20%3D%200)
Divide both sides of the equation by 2
2x/2 = 0/2
x = 0
(4+612+x)=2(3x+8)
4+612+x=6x+16
4+612-16=6x-x
600=5x
Divide both sides of the equation by 5
600/5 = 5x
120 = x
Answer:
x < 1
Step-by-step explanation:
3x + 2<5 (subtract 2 on each side)
3x< 3 (Divide 3 on both sides)
x < 1
Answer:
If you add the same unknown to the triple unknown you will get 485 finds unknown.
Step-by-step explanation:
Here try watching this: https://www.khanacademy.org/math/algebra/x2f8bb11595b61c86:systems-of-equations/x2f8bb11595b61c86:systems-of-equations-word-problems/v/substitution-method-3